Menggali Makna Salam Jien Sho Sebagai Media Dakwah Non-Verbal Pada IKS.PI Kera Sakti - Makhmud Sholih; Siti Robiah Adawiyah (Jurnal Dakwah dan Masyarakat, 2026)
This research aims to uncover the symbolic meaning of Salam Jien Sho, analyze its function as a non-verbal da'wah medium, and explain its contribution in the formation of spiritual and moral character of IKS members. PI Kera Sakti. This study is motivated by the importance of developing a cultural da'wah model that utilizes local cultural symbols and practices as a medium for internalizing Islamic values in modern society. The research uses a qualitative method with a descriptive approach. Data was obtained through observation, in-depth interviews with trainers and members of IKS. PI Kera Sakti, as well as documentation of various organizational activities. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing with triangulation techniques of sources and methods to ensure the validity of the data. The results of the study show that Salam Jien Sho contains a symbolic meaning that represents a balance between respect, tawadhuan, steadfastness of faith, and self-control. The open left hand symbolizes respect for God, parents, teachers, and others, while the clenched right hand symbolizes moral strength, discipline, and commitment to practicing religious teachings. The union of the two symbols forms a harmony between morals and spiritual strength that is the ideal character of a warrior. In addition to functioning as an organizational identity, Salam Jien Sho is also an effective non-verbal da'wah medium in internalizing Islamic values through the cultural practice of pencak silat. This finding confirms that local cultural symbols can be a relevant da'wah instrument in character development and strengthening community spirituality. Penelitian ini bertujuan untuk mengungkap makna simbolik Salam Jien Sho, menganalisis fungsinya sebagai media dakwah non-verbal, serta menjelaskan kontribusinya dalam pembentukan karakter spiritual dan moral anggota IKS.PI Kera Sakti. Kajian ini dilatarbelakangi oleh pentingnya pengembangan model dakwah kultural yang memanfaatkan simbol dan praktik budaya lokal sebagai media internalisasi nilai-nilai Islam di tengah masyarakat modern. Penelitian menggunakan metode kualitatif dengan pendekatan deskriptif. Data diperoleh melalui observasi, wawancara mendalam dengan pelatih dan anggota IKS.PI Kera Sakti, serta dokumentasi berbagai aktivitas organisasi. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan dengan teknik triangulasi sumber dan metode untuk menjamin keabsahan data. Hasil penelitian menunjukkan bahwa Salam Jien Sho mengandung makna simbolik yang merepresentasikan keseimbangan antara penghormatan, ketawadhuan, keteguhan iman, dan pengendalian diri. Tangan kiri yang terbuka melambangkan penghormatan kepada Allah, orang tua, guru, dan sesama, sedangkan tangan kanan yang mengepal melambangkan kekuatan moral, disiplin, dan komitmen menjalankan ajaran agama. Penyatuan kedua simbol tersebut membentuk harmoni antara akhlak dan kekuatan spiritual yang menjadi karakter ideal seorang pendekar. Selain berfungsi sebagai identitas organisasi, Salam Jien Sho juga menjadi media dakwah non-verbal yang efektif dalam menginternalisasikan nilai-nilai keislaman melalui praktik budaya pencak silat. Temuan ini menegaskan bahwa simbol budaya lokal dapat menjadi instrumen dakwah yang relevan dalam pembinaan karakter dan penguatan spiritualitas masyarakat.